#Architecturez: Rackz, Shackz and the Opportunities In Between. (4th January 2021) - Barnes, Mat
Abstract: Mat Barnes is a director of London‐based architectural practice CAN. He believes ill‐conceived, expedient parts of cities – the bits that are unplanned and left to their own devices – are fecund breeding grounds for formal and material innovation. These are places of happy collisions of architectural elements that are ripe for further architectural insertions and experiments. Here he presents some of his practice's work in such contexts.